RUANG BANACH PADA RUANG BARISAN 1  , p  DAN  - Alwi, Wahidah (Teknosains: Media Informasi Sains dan Teknologi, 2014)
The main object of the vectors are the vectors can be added together and generate a vector, and produces a number is multiplied by another vector. Any set of objects with properties like this are called "vector space". Mathematical structure to be defined is a Banach space. Clearly defined Banach space vector space of real / complex normed and complete (with respect to the norm). Banach space in this study examined the sequence space 1  , p  and   . Based on the purpose of this study is to assess the Banach space within a sequence space 1  , p  and   , it is obtained that a sequence space 1  , p  and   form Banach space if it meets the requirements of that sequence space 1  , p  and   is a vector space, normed sequence space, and normed sequence space with complete.